Tingkat Kebugaran Jasmani Siswa Sekolah Dasar di Daerah Dataran Sedang - Sani, Muhammad Luthfi; Hariadi, Imam (Universitas Negeri Malang, 2020)
Abstract: The purpose of this study was to determine the level of physical fitness of students of SD Negeri Wajak 2 and 6. The method used in this study was descriptive quantitative and the population used was 134 students consisting of grades 2 to 6 with ages 6 to 12 years. This sampling technique uses total sampling or all subjects are used as samples by using a 20-meter sprint test instrument, shuttle run, flaminggo balance test, tapping test plate, and sit and reach. Data analysis using quantitative descriptive, from the results of data analysis that has been carried out and the discussion made, the level of physical fitness of elementary students in the plain area is entering the category of